Research Trends in the Last 3 years Related to Distance Education : A Bibliometric Study - Dewi Andriyani; Susy Puspitasari; Titi Chandrawati; Syahrul Ramadhan (Universitas Pendidikan Mandalika, 2023)
This study aims to analyze the research trends related to distance education over the past three years by examining the publication patterns and key topics within the field. This study used a quantitative descriptive research approach with a bibliometric method. Data was collected through the Scopus database with the keyword